Tournament Mechanism in Wine-Grape Contracts: Evidence from a French Wine Cooperative*. (16th December 2014) - Fares, M'hand; Orozco, Luis
Abstract This article analyzes the contractual relationship between a wine cooperative (winery) and its member (growers). This relationship is plagued by moral hazard and adverse selection problems in grape quality. Indeed, growers can be opportunistic since the cooperative is unable to observe: (1) their effort level due to imperfect monitoring technology; and (2) their productive abilities (types) due to adverse selection. Because the growers' vineyard practices and efforts are one of the main determinants of grape quality, the cooperative implements an incentive compensation system to induce growers to make the maximum effort toward the achievement of quality. This compensation scheme is similar to that in tournaments (Green and Stokey, 1983; Knoeber, 1989; Lazear and Rosen, 1981; Prendergast, 1999). In our case, the cooperative promotes competition between growers by offering a promotion to a higher-quality contract, while, at the same time, organizing the contest by creating homogeneous groups of growers using a menu of contracts and monitoring through regular visits to the vineyard. Using a database of 1, 219 contracts, we test the effect of: (1) the cooperative's tournament compensation scheme; (2) the menu of contracts and monitoring mechanism. The results of our econometric estimations provide some confirmation of both effects. (JEL classifications: L14, D82, Q13)